GLOVOCS - Master compound assignment guide for proton transfer reaction mass spectrometry users. (1st January 2021) - Yáñez-Serrano, A.M.; Filella, I.; LLusià, J.; Gargallo-Garriga, A.; Granda, V.; Bourtsoukidis, E.; Williams, J.; Seco, R.; Cappellin, L.; Werner, C.; de Gouw, J.; Peñuelas, J.
Abstract: The richness of measurements obtained by Proton-Transfer Reactions Mass Spectrometry (PTR-MS) has opened a new paradigm for the quantification of volatile organic compounds (VOCs). A wide range of compounds can be monitored, however, each detected signal is subject to a compound assignment instead of actual identification because PTR techniques are mass-selective and isomers cannot be separately measured. Thus, rapid development in the field requests continued community efforts to identify compounds. In this study we have reviewed the available literature and created a master compound assignment guide called GLOVOCS that can be referred to by PTR-MS practitioners. GLOVOCS is aimed to help in advancing science of VOCs by facilitating the research of multiple groups using PTR-MS to monitor VOCs and to disentangle the physical, chemical and biological mechanisms underlying their production, emission and impact on environment and organisms from bacteria to humans. The guide is freely accessible at http://glovocs.creaf.cat as a collaborative tool, where users can both consult and contribute to the identification of VOCs by providing possible candidates for all chemical formulas from 18 to 330 atomic mass units. When available, we indicate if there is evidence for biogenic or anthropogenic VOC origin, as well as grouping the compounds based on the Classyfire chemotaxonomic classification (Djoumbou Feunang et al., 2016). While GLOVOCS aims to facilitate the first assessment and consistent classification of compounds, we highly recommend further cross-validation for verifying compounds when using PTR-MS techniques. Highlights: We have created GLOVOCS, a master compound assignment guide that can be referred to by PTR-MS practitioners. GLOVOCS is aimed to help in advancing science of VOCs by facilitating the research of multiple groups using PTR-MS. GLOVOCS, accessible at http://glovocs.creaf.cat, is a collaborative tool where users can both consult and contribute to.